2005
DOI: 10.1097/01.ju.0000162037.49102.56
|View full text |Cite
|
Sign up to set email alerts
|

Permeation of Hypericin in Spheroids Composed of Different Grade Transitional Cell Carcinoma Cell Lines and Normal Human Urothelial Cells

Abstract: Loss of E-cadherin expression correlates with loss of intercellular adhesion, tight junction formation and enhanced paracellular transport. The data show that E-cadherin hampers the permeation of hypericin in spheroids and the loss of intercellular adhesion, present in superficial bladder cancer lesions, can be associated with enhanced hypericin permeation. Therefore, E-cadherin expression seems to have a pivotal role in the selective uptake of hypericin after intravesical instillation in human bladders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 15 publications
3
27
0
Order By: Relevance
“…[11][12][13] The mechanism underlying the tumoritropic characteristics of the selectivity is not fully understood. It is assumed that the enhanced uptake of hypericin is secondary to a loss of intercellular adhesion in malignant tissue (e.g., by a decreased expression of E-cadherin in cancer cells 14,15 ), resulting in an enhanced intralesional migration of the compound by a paracellular route.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The mechanism underlying the tumoritropic characteristics of the selectivity is not fully understood. It is assumed that the enhanced uptake of hypericin is secondary to a loss of intercellular adhesion in malignant tissue (e.g., by a decreased expression of E-cadherin in cancer cells 14,15 ), resulting in an enhanced intralesional migration of the compound by a paracellular route.…”
Section: Introductionmentioning
confidence: 99%
“…Preparation and characterization of urothelial cultures was done as previously described (47,48). Briefly, TRPV4 +/+ and TRPV4 -/-mice were catheterized and sacrificed.…”
Section: Figurementioning
confidence: 99%
“…In addition to the fact that intracellular uptake of HY is higher in cancerous cells, subsequent studies unraveled other possible contributing factors to its selective accumulation at tissue level 30,68. For instance, Huygens et al 30.…”
Section: Photodynamic Properties Of Hypericinmentioning
confidence: 99%
“…For instance, Huygens et al 30. studied human bladder cell carcinoma using a 3-dimensional (3D) spheroid model, and reported that the loss in intercellular adhesion due to the reduced expression of a transmembrane adhesion protein, E-cadherin, plays a pivotal role in the selective uptake of HY.…”
Section: Photodynamic Properties Of Hypericinmentioning
confidence: 99%